Analisis Pengaruh Bentuk Telapak Kaki Terhadap Kelelahan Fisik - Herianto Herianto (Universitas Gadjah Mada, 2013)
Physical activity over time can cause fatigue during exercise such as walking or light running. Physical fatigue effects on heart rate and blood pressure. Factors that can cause fatigue are gender, cardiovascular disease status, sport exercise habits, BMI (Body Mass Index) and study activities during a week. Physical fatigue also could be caused by factors shape of your foot, especially the form of flat feet/pesplanus in type 1, 2or 3. Subjects of this research were students of Industrial Engineering Gadjah Mada University ages 19 to 23 years with the aim of sampling techniques to the criteria of having normal or flat feet. The subjects run normally using a tread mill with a speed of 4 miles per hour for 6 minutes. The variables measured were heart rate and blood pressure. Heart rate was measured in three sessions among others before, during and after the experiment using a heart rate monitor while blood pressure was measured before and after the experiment. There are significant differences in systolic blood pressure before and after the experimental on indicator of sex, heart rate after experimental on indicator of disease status and heart rate on indicator exercise habit for normal feet. Then in the form of pesplanus foot type 1, there are significant differences like systolic and diastolic blood pressure after experimental on indicator of BMI (Body Mass Index) and systolic blood pressure on indicator of pre-experimental study activities during a week, in which a significant difference in respondents who did not have study activities of the respondents who went tocollegein6-10 hours. In the form of pesplanus foot type 2 there is a significant difference in heart rate when experimental on indicator of cardiovascular disease status.